Respuesta :

Answer:

x=-2 OR x=-4

Step-by-step explanation:

Step 1: Subtract -6x from both sides.

x2+8−−6x=−6x−−6x

x2+6x+8=0

Step 2: Factor left side of equation.

(x+2)(x+4)=0

Step 3: Set factors equal to 0.

x+2=0 or x+4=0

x=−2 or x=−4

Good luck! Hope this helps!

Step-by-step explanation:

[tex] {x}^{2} + 8 - ( - 6x) = 0 \\ x {}^{2} + 8 + 6x= 0 \\ x { }^{2} + 6x + 8 = 0 \\ x {}^{2} + 4x + 2x + 8 = 0 \\ x(x + 4) + 2(x + 4) = 0 \\ (x + 4)(x + 2) = 0 \\ either \\ x + 4 = 0 \\ x = - 4 \\ or \\ x + 2 = 0 \\ x = - 2 \\ hence. \\ x = - 4and - 2[/tex]